2019
DOI: 10.1021/acsnano.9b03278
|View full text |Cite
|
Sign up to set email alerts
|

Robust Piezo-Phototronic Effect in Multilayer γ-InSe for High-Performance Self-Powered Flexible Photodetectors

Abstract: The piezo-phototronic effect has been promising as an effective means to improve the performance of two-dimensional (2D) semiconductor based optoelectronic devices. However, the current reported monolayer 2D semiconductors are not regarded as suitable for actual flexible piezotronic photodetectors due to their insufficient optical absorption and mechanical durability, although they possess strong piezoelectricity. In this work, we demonstrate that, unlike 2H-phase transition-metal dichalcogenides, γ-phase InSe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(138 citation statements)
references
References 50 publications
5
125
0
Order By: Relevance
“…Recently, the analogous experiment was also performed on 2D multilayer γ-phase InSe photodetector. The responsivity and response speed of this photodetector were enhanced further by as much as 696% and 1010% when the device was subjected to a 0.62% uniaxial tensile strain due to the piezo-phototronic effect [204]. Zhang et al [205] designed and fabricated a flexible photodiode based on single-layer MoS 2 lateral p-n homojunction by chemical doping (Fig.…”
Section: Tuning the Performance Of Photodetector By Piezoelectric Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the analogous experiment was also performed on 2D multilayer γ-phase InSe photodetector. The responsivity and response speed of this photodetector were enhanced further by as much as 696% and 1010% when the device was subjected to a 0.62% uniaxial tensile strain due to the piezo-phototronic effect [204]. Zhang et al [205] designed and fabricated a flexible photodiode based on single-layer MoS 2 lateral p-n homojunction by chemical doping (Fig.…”
Section: Tuning the Performance Of Photodetector By Piezoelectric Effectmentioning
confidence: 99%
“…Figure 17e, f shows the device under 0.65% tensile strain, the photoresponsivity increase from 0.22 to 0.37 A W −1 and the photo-response time decrease from 244 to 214 μs. Dai et al [204] demonstrated the photocurrent of β-InSe multilayers-based photodetector achieved a 211% enhancement ratio under a uniaxial tensile strain of 0.62% due to piezoresistive effect. The piezoresistive effect in 2D semiconductors can reduce the barrier heights of two Schottky junctions simultaneously (Fig.…”
Section: Tuning the Performance Of Photodetector By Piezoresistive Efmentioning
confidence: 99%
“…With 0.31% tensile strain (see Figure 6d), the photodetector exhibited an ultrahigh photoresponsivity of 824 mA W −1 under the 400 nm illuminations at zero bias, a high detectivity of 1.7 × 10 12 Jones, and a high response speed of 20 µs. [ 118 ] Moreover, Pal et al. proposed a plasmonic Au nanoparticle loaded g‐C 3 N 4 over CdS/ZnO heterojunction, leveraging the piezophototronic effect.…”
Section: Piezophototronic Effect and Its Applications For 2d Materialsmentioning
confidence: 99%
“…We also compare the performance parameters of NIO device with some previously reported flexible perovskite and inorganic materials‐based photodetectors (Figure 3f). [ 21,41–48 ] The detailed parameters are supplemented in Table S2 (Supporting Information). Obviously, the figure of merits of NIO device are comparable to and even higher than most of those devices.…”
Section: Figurementioning
confidence: 99%